Penggunaan Metode Port Knocking untuk Meningkatkan Sistem Keamanan Jaringan Komputer - Ardian Fachreza (Lembaga Pengembangan Kinerja Dosen, 2025)
The advancement of communication and information technology demands improved computer network security to protect data from various threats such as hacker attacks and DDoS that exploit open ports. A strong security system is crucial because computer networks are vulnerable to eavesdropping and data manipulation during transmission. This research highlights the use of the Port Knocking method as an effective solution to enhance computer network security. The research employs a qualitative descriptive approach with a literature review. The author analyzes and concludes the effectiveness of port knocking in improving network security. The results show that the port knocking method effectively increases network security by closing unused ports and only allowing access to authorized users. Implementation of port knocking on Mikrotik routers successfully reduces the risk of brute force attacks and intrusions that can disrupt network connectivity. A case study at LKP Surya Computer demonstrates that this method can strengthen network security and prevent unauthorized access that could potentially damage router configurations.